Efficacy of calcium lactate as a biodegradable coagulant for peat water purification: an experiment comparative study - Asmadi, Asmadi; Akhmadi, Zainal; Suharno, Suharno; Yulia, Yulia (International Journal of Public Health Science (IJPHS), 2025)
Kalimantan relies significantly on peat water as a water source. However, due to its high organic content, acidic nature, and intense color, it is not safe to drink. To address this issue, researchers proposed an eco-friendly coagulant, calcium lactate, to remove suspended solids. To test its effectiveness, the coagulant was compared to membrane technologies, specifically nanofiltration (NF) and reverse osmosis (RO), at Rasau Jaya General Hospital in West Kalimantan between April and October 2022. Different pressures, 40, 60, and 80 Psi, were used to test both methods. Before and after treatment, the levels of total coliform, E. coli, pH, total dissolved solid (TDS), turbidity, color, and calcium were examined. The results showed that the best outcomes were achieved at 60 Psi. The combination of 0.8 mg/l calcium lactate and NF met all the standard values, except for color (29 TCU). Calcium lactate and RO, however, produced safe drinking water at 60 Psi from all analyzed parameters (E. coli=0, total coliform=0, pH=6.5, TDS=7.1, nephelometric turbidity units (NTU)=2.8 NTU, color=8.7 TCU, and calcium 7.6 mg/l). The reduction of bacteriological substances achieved 100% for both methods. Overall, the combination of calcium lactate and RO yielded slightly better results than NF.